واقع ممارسات إدارة المعرفة في بيئة التعلم الإلكتروني في ضوء مستحدثات تطبيقات الذكاء الاصطناعي في جامعة الملك عبدالعزيز - القايد، أشواق قايد; ضليمي، سوسن طه حسن; الرباعي، أمين علي (مركز البحث وتطوير الموارد البشرية - رماح, 2022)
هدفت الدراسة إلى التعرف على واقع ممارسات إدارة المعرفة في بيئة التعلم الإلكتروني في ضوء مستحدثات تطبيقات الذكاء الاصطناعي في جامعة الملك عبد العزيز، وذلك من خلال تقصي تصور الأكاديميين في جامعة الملك عبد العزيز حول الأدوار التي قد تلعبها تقنيات الذكاء الاصطناعي في أتمته عمليات التعلم الإلكتروني وربط ذلك بعمليات إدارة المعرفة، وقد استخدمت الباحثة للدراسة المنهج الوثائقي ومنهج دراسة الحالات المتعددة ومنهج دراسة الحالة، وتكون مجتمع الدراسة (6649) من الأكاديميين بجامعة الملك عبد العزيز، تم اختيار (436) كعينة للدراسة حيث تم اختيارها بالطريقة العشوائية، كما تبين من نتائج الدراسة أن المتوسط العام الاستجابات الأكاديميين حول تصوراتهم بلغ (4.15) بقيمة عالية، حيث جاء بعد "التخزين" بالمرتبة الأولى وبدرجة عالية جدا بلغت قيمة متوسطها الحسابي (4.22) وجاءت الأبعاد الأخرى في هذا المحور بدرجات عالية تراوحت المتوسطات الحسابية لها من (4.17-4.09) والتي كانت على ترتيبها "التطبيق والاستخدام ثم الاكتساب والتشخيص والمشاركة"، جاء بعد "التوليد" بالرتبة الأخيرة وبدرجة عالية من حيث تصور الدور حيث بلغت قيمة متوسطها الحسابي (4.9)، وتدل على أنه كلما زادت درجات تقدير الأكاديميين لمستويات معرفتهم ومهاراتهم باستخدام تطبيقات الذكاء الاصطناعي وإدارة المعرفة في نظام التعلم الإلكتروني، حيث كانت أعلى قيمة ارتباط لمستويات المعرفة والمهارة المرتبطة باستخدام تطبيقات الذكاء الاصطناعي وإدارة المعرفة في نظام التعلم الإلكتروني بجامعة الملك عبد العزيز مع بعد الاكتساب (0.62) وهي قيمة دالة إحصائيا عند مستوى الدلالة (0.01) بينما تراوحت قيم الارتباطات لعمليات (التطبيق والاستخدام، والتشخيص، المشاركة، التخزين) من (0.59-0.51) وهي قيم دالة إحصائيا عند مستوى الدلالة (0.01) وجاء ارتباطها ببعد التوليد بالرتبة الأخيرة حيث بلغت قيمة ارتباطها (0.49) وهي قيمة دالة إحصائيا، كما توصلت الدراسة إلى مجموعه من التوصيات من أهمها ضرورة توظيف تطبيقات الذكاء الاصطناعي في المؤسسات التعليمية واستخدامها في مجالات العملية التعليمية المختلفة، أيضًا ضرورة عقد مؤتمرات حول كيفية مساهمة تقنيات الذكاء الاصطناعي في بيئة التعلم الإلكتروني في الرقي بالعملية التعليمية، وحث الكادر التعليمي على توظيفات تقنيات الذكاء الاصطناعي لخدمة العملية التعليمية، ولتسهيل عملية التعلم لدى الطلبة. The study aimed to identify The reality of knowledge management practices in the e-learning environment in the light of the innovations of intelligence applications at King Abdulaziz University, by investigating the perception of academics at King Abdulaziz University about the roles that artificial intelligence techniques may play in automating e-learning processes and linking this to knowledge management processes. For the study, the documentary approach, the multiple case study approach, and the case study approach, and we make up the study population (6,649) of academics at King Abdulaziz University, (436) were chosen as a sample for the study, where they were chosen randomly. It reached (4.15) with a high value, where the "storage" dimension came in the first place and with a very high degree its arithmetic average value reached (4.22) and the other dimensions in this axis came in high degrees, their arithmetic averages ranged from (4.17-4.09), which were ranked by "Application, Use, Acquisition, Diagnosis, and Participation", the "generation" dimension came in the last rank and with a high degree in terms of the perception of the role, as its arithmetic mean value reached (4.09), and it indicates that the more knowledge on this, the degrees of academics’ appreciation of their knowledge and skills levels using artificial intelligence applications and knowledge management in the e-learning system, where the highest correlation value was for the levels of knowledge and skill associated with the use of artificial intelligence applications and knowledge management in the e-learning system at King Abdulaziz University with the acquisition dimension (0.62), which is a value, statistically, significant at the significance level (0.01), while the correlations values for the processes (application, use, diagnosis, sharing, storage) ranged from (0.59-0.51), and they are statistically significant values at the significance level (0.01). The last Generation, as its correlation value was (0.49), which is a statistically significant value. The study also found there is a real need to employ artificial intelligence applications in educational institutions in order to using them in various fields of the educational process, as well as the need to hold conferences on how artificial intelligence techniques contribute to the learning environment. To improve the educational process, and urge the educational staff to employ artificial intelligence techniques is essential to serve the educational process, and to facilitate the learning process for students.
Keywords: العملية التعليمية -- بيئة التعلم الرقمي -- إدارة المعرفة -- الذكاء الإصطناعي